DIGITAL MARKETING STRATEGIES: LEVERAGING AI TECHNOLOGY TO ENHANCE EFFECTIVENESS IN ADDRESSING GLOBAL CRISES - Youwangka, Raden Khemal (Ikatan Dosen Menulis, 2024)
Digital marketing strategies have become an essential tool for businesses to navigate and respond effectively to global crises. The integration of Artificial Intelligence (AI) technology in these strategies offers unprecedented opportunities to enhance marketing effectiveness during uncertain times. This literature review explores the role of AI in digital marketing, focusing on its potential to improve decision-making, customer engagement, and crisis response. By examining previous studies and theoretical frameworks, the review identifies key AI applications such as predictive analytics, automation, and personalized marketing. It highlights how AI-powered strategies can be leveraged to address the challenges posed by global crises, including economic downturns, pandemics, and social unrest. The review also discusses the benefits and limitations of AI in marketing, particularly in terms of ethical considerations and data privacy. Furthermore, it offers insights into the future of digital marketing in a crisis context, emphasizing the need for adaptive strategies. This article contributes to the understanding of AI's transformative role in modern marketing practices and provides recommendations for businesses seeking to enhance their crisis management efforts. Ultimately, the findings suggest that AI technology can be a critical enabler in ensuring marketing strategies are resilient and effective in a rapidly changing world.